European business ethics casebook the morality of corporate decision making - Dubbink, Wim; Liedekerke, Luc; Luijk, Henk (Issues in business ethics, 2011)
Business cases are at the heart of business ethics as a discipline. Analysis and reflection on the morality of business often is triggered by concrete cases. After four introductory chapters into recent developments within business ethics and the value of case analysis, the present volume offers extensive description of eight recent European cases, mainly stemming from The Netherlands and Belgium and all of them with a clear moral impact. Among them are the Lernout and Hauspie speech technology disaster, Heineken struggle with the promotion girls selling beer in Cambodia, cartels in the Dutch construction industry, the pharmaceutical industry and the Aids crisis, and Unilever allegedly making use of child labour in the cotton industry in India. The book will be of interest to researchers as well as teachers of undergraduate and graduate courses in Business Ethics, Business in Society, Management and Organisation Theory and Strategic Management. It will also be useful for business practitioners eager to learn about business ethics by means of cases.